Pyroelectric properties of ferroelectric composites based on polyvinylidene fluoride (PVDF) with graphene and graphene oxide. (12th March 2019) - Bystrov, V. S.; Bdikin, I. K.; Silibin, M. V.; Meng, X. J.; Lin, T.; Wang, J. L.; Karpinsky, D. V.; Bystrova, A. V.; Paramonova, E. V.
Abstract: Novel composites based on polymer ferroelectrics with graphene (G) and graphene oxide (GO) have many advantages over pristine materials. In this work, the results of the computational molecular modeling of the composite nanostructures are presented and analyzed. The calculations were focused on pyroelectric properties of the composites based on polyvinylidene fluoride (PVDF) films with G/GO layers. The pyroelectric effect was modeled and pyroelectric coefficients were calculated for several models using molecular dynamics simulation with quantum-chemical semi-empirical PM3 method from HyperChem tool. The obtained results present a new prospective for further studies of the ferroelectric polymer-graphene multifunctional nanomaterials and their applications.